Ograniczenia nabywania nieruchomości przez cudzoziemców w Polsce a swoboda przepływu kapitału - Muzyka, Małgorzata (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2019)
The article presents the Author point of view on the legal protection, freedom, restrictions on the acquisition real property by foreigners in Poland. Any acquisition of real property in the member states should directly follow from the provisions of the TFEU. The text is based on the opinion the Court of Justice of the European Union and European Union law.
Keywords: free movement of capital; common market; European Union; internal market; real property